Análisis de la desvalorización territorial en el sector del aeropuerto Ernesto Cortissoz (2019)
The municipality of Soledad is a territory that has hosted citizens from all corners of Colombia, due to its geographical location and lack of administrative control of informal settlements. Studies re-veal that one of the causes for the diversity of the inhabitants in solitude is "arriagada" in the intensification of the war, which has led to the generation of illegal invasions, many occupied by dis-placed peasants, and by mistaken extensions not conceived with partial plans. In the case of the Ernesto Cortissoz airport sector, this research is oriented to raise from an urban perspective, the costs generated by this bad prevention of illegal occupation of land and the loss of competitiveness in front of neighboring municipalities, having a logistical potential in projection to carry out in the sector. In the following article the results are developed that allow the real-ization of graphs and cartographies with the purpose of analyzing the general approach of the urbanistic change and the proposal of the sector is determined, where the variants are analyzed and they propose values not only in pesos but in competition, dissipated by the lack of structuring a strategy of urban renovation involving the public and private entity. And ending with a structured explanation of how the acquisition and analysis of cartographic, real estate and socioeconomic information will be processed